Intergenerational Learning Dynamics and the Perspective Transformation of Generation Alpha Students toward Generation Z Student Teachers - Ayu Rahmawati; Triana Lestari; Dede Margo Irianto (Universitas Sebelas Maret, 2026)
The interaction between Generation Alpha students and Generation Z student teachers creates new relational dynamics that may influence how students perceive communication, closeness, and authority in learning. Although this phenomenon is becoming increasingly common in elementary schools, it has rarely been studied from the students’ perspective. This study aims to explore Generation Alpha students’ responses to intergenerational interactions in elementary schools. Using a qualitative Interpretative Phenomenological Analysis (IPA) approach within an interpretivist paradigm, the study observed six fifth-grade students and involved student teachers as informants. Data were collected through eight weeks of non-participant observation and semi-structured interviews, and were subsequently analyzed using NVivo through the stages of compiling, disassembling, reassembling, interpreting, and concluding. The data analysis yielded three key themes: (1) Generation Z student teachers are perceived as egalitarian, supportive, and approachable figures; (2) social-emotional attachment enhances students’ comfort, participation, and engagement; and (3) intensive closeness shifts the boundaries of the formal teacher–student relationship into a friendship-like relationship, thereby transforming the meaning of authority in the classroom. The findings indicate that intergenerational relationships reshape pedagogical relations in elementary schools. Understanding these dynamics is important for schools, student teachers, and teacher education programs in developing mentoring strategies and policies that balance relational closeness with pedagogical authority.